Comparison of Rule-Based and DTMRI-Derived Fibre Architecture in a Whole Rat Ventricular Computational Model - Bishop, M; Hales, P; Plank, G; Gavaghan, D; Scheider, J; Grau, V (2009)
The anisotropic electrical conduction within myocardial tissue due to preferential cardiac myocyte orientation ('fibre orientation) is known to impact strongly in electrical wavefront dynamics, particularly during arrhythmogenesis. Faithful representation of cardiac fibre architecture within computational cardiac models which seek to investigate such phenomena is thus imperative. Drawbacks in derivation of fibre structure from imaging modalities often render rule-based representations based on a priori knowledge preferential. However, the validity of using such rule-based approaches within whole ventricular models remains unclear. Here, we present the development of a generic computational framework to directly compare the fibre architecture predicted by rule-based methods used within whole ventricular models against fibre structure derived from DTMRI data, and assess how relative differences influence propagation dynamics throughout the ventricles. Results demonstrate the close overall match between the methods within the rat ventricles, and highlight regions for potential rule-adaption. © 2009 Springer Berlin Heidelberg.